PENGARUH PEMBERIAN PAKAN DENGAN KANDUNGAN PROTEIN BERBEDA TERHADAP PERTUMBUHAN IKAN BANDENG (Chanos chanos) Effect of Different Feed Protein Levels on Growth of Milk Fish (Chanos chanos) - Muhammad Ambia; Eriyusni Eriyusni; Irwanmay Irwanmay (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Chanos chanos is one of the consumed fish, and very populer in Indonesiapopulated, easy to growth and very cheap. These studies were give different ofprotein levels. The protein feed were used comercial feed with 30 % and 16 %composition of protein, the growth of fish were observed from june-august 2014 inthe Rawamas village Nurusalam subdistrict Aceh Timur regency. The analysis of datawere used SPSS Versi 22. The results showed that fish feed with protein 30 % highestbody weight than fish feed with protein 16 %, with regard to growth andconformation. Mean and standart error of growth highest body weight 56,4cm, lengthof 20,9 cm and water temperature range 28 – 29 c, ph 7 – 7,2 salinity 29,3 – 30 pptand do 6,66 – 6,79 mg/l.Keywords : Chanos chanos, Feed, Growth.